The support for farmer-led seed systems in African seed laws. - Herpers, S.; Vodouhe, R.S.; Halewood, Michael; Jonge, B. de (ISSD Africa, 2017)
The synthesis report is part of a series of papers on Integrated Seed Sector Development (ISSD) in Africa’s thematic working group on Matching national realities with global commitments. The thematic working group addressed the main question on how African governments implement their global commitments while fostering a viable pluralistic sector. The main hypothesis was that making these commitments more coherent with the practices and realities of farmers and creating an enabling environment for strengthening multiple seed systems will increase farmers’ access to quality seed. Three main topics were discussed under this theme: access and benefit sharing for climate resilient seed systems; national and regional seed laws that support the development of a robust, integrated seed sector that supports smallholder farmers' needs; and creating room for informal and intermediary seed systems in a UPOV '91 informed Plant Variety Protection system.